-(5p+6)-2(-7p-9)=

Simple and best practice solution for -(5p+6)-2(-7p-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5p+6)-2(-7p-9)= equation:


Simplifying
-1(5p + 6) + -2(-7p + -9) = 0

Reorder the terms:
-1(6 + 5p) + -2(-7p + -9) = 0
(6 * -1 + 5p * -1) + -2(-7p + -9) = 0
(-6 + -5p) + -2(-7p + -9) = 0

Reorder the terms:
-6 + -5p + -2(-9 + -7p) = 0
-6 + -5p + (-9 * -2 + -7p * -2) = 0
-6 + -5p + (18 + 14p) = 0

Reorder the terms:
-6 + 18 + -5p + 14p = 0

Combine like terms: -6 + 18 = 12
12 + -5p + 14p = 0

Combine like terms: -5p + 14p = 9p
12 + 9p = 0

Solving
12 + 9p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 9p = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 9p = 0 + -12
9p = 0 + -12

Combine like terms: 0 + -12 = -12
9p = -12

Divide each side by '9'.
p = -1.333333333

Simplifying
p = -1.333333333

See similar equations:

| 9x^2=2x+25+8x^2+8x | | -4y+3y-8=10 | | (2t-9)(2t+9)= | | 6[g+3]=-2[g+3] | | v(x)=4x^3-20x^2+24x | | 16x^2-x^2=15x^2 | | 9(x-2)=-9 | | b+-3=-5 | | 45x-3x^2=0 | | 3(58-8)=x | | 6.83-c=3.83 | | 6x+6y=7.50 | | 6x-8x+2x-5x= | | 25x^2-x^2=16x^2 | | -9-6x=2.3(14x+35) | | 9(42)-9(4)=9(30)+9(x) | | 5cos(x)-3=cos(2x) | | f(x)=2x+4y | | 42+5*-21=3*-21 | | 3.71(p-14)+8=15.42 | | 2.9(v+1)+4=18.5 | | -x+5(5)=19 | | 319=26(u-994)+345 | | 5x^2+12x+12=0 | | 3(y-563)+45=969 | | -9(n-18)=144 | | 2x-11=x+64 | | 3sinx+2cosx-3=0 | | 3-p=7.4 | | 7(y-3)=7 | | 9c+c-6= | | 4x^2-4=2x-1 |

Equations solver categories